2022
DOI: 10.1177/00048674221107872
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and determinants of mental health related to climate change in Australia

Abstract: Aims: The climate emergency will likely prove this century’s greatest threat to public health within which mental health effects need consideration. While studies consistently show the majority of Australians are very concerned about the impacts of climate change, there is limited evidence from nation-wide research linking climate change with mental health burden in sub-populations. This study aimed to understand the impact of climate change on mental health in the Australian population and identify population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 41 publications
0
34
0
Order By: Relevance
“…Recent research has demonstrated that climate anxiety is an increasingly common experience, and while certainly not restricted to, appears to be especially prominent among younger generations (5,8,15,39,40). We have previously reported on young people's experiences with and feelings about climate change as compared to the COVID-19 pandemic, demonstrating that, in spite of the more direct impact on their day-to-day lives, pandemic worries were -to some extent -overshadowed by young people's continuing concern about climate change (10).…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has demonstrated that climate anxiety is an increasingly common experience, and while certainly not restricted to, appears to be especially prominent among younger generations (5,8,15,39,40). We have previously reported on young people's experiences with and feelings about climate change as compared to the COVID-19 pandemic, demonstrating that, in spite of the more direct impact on their day-to-day lives, pandemic worries were -to some extent -overshadowed by young people's continuing concern about climate change (10).…”
Section: Discussionmentioning
confidence: 99%
“…The young seems to be more vulnerable to certain psychological consequence to climate event [37], such as psychoterratic syndromes and climate related distress [38 ▪ ], or pretrauma symptoms and distress caused by the loss of advantageous land [15] even if they are not directly exposed to visible consequences or live in big cities, which may not represent a protective effect. In case of direct exposure to climate change-related events, they show PTSD symptoms, higher intensity of emotional stress, feeling of hopelessness, powerlessness, alarm.…”
Section: Disadvantaged Populationsmentioning
confidence: 99%
“…Environmental crises such as climate change elevate health vulnerability, especially mental health risks, leading to emotions such as anxiety, depression, and helplessness. Patrick et al (2022)'s study on nationwide survey in Australia on the impact of climate change on mental health identified the population groups that are most at risk of climate-related mental health issues. According to this study, climate change-related mental health issues disproportionately affect women, young people, those from disadvantaged regions, and those who have experienced climate change-related extreme events.…”
Section: Women's Rights and Risksmentioning
confidence: 99%